Pooled safety and efficacy of inclisiran in patients with statin intolerance (ORION-10 and ORION-11). (25th November 2020) - Wright, R.S; Kallend, D; Raal, F.J; Stoekenbroek, R; Koenig, W; Leiter, L.A; Landmesser, U; Schwartz, G; Wijngaard, P.L.J; Kastelein, J.J.P; Ray, K.K
Abstract: Introduction: Statin-associated side effects prevent a substantial proportion of patients from being adequately treated with statin therapy and achieving adequate LDL-C reductions. Phase 3 trials showed that inclisiran, a new siRNA, durably lowers LDL-C by ≥50% on top of maximally tolerated statin therapy. Purpose: To evaluate inclisiran's tolerability and LDL-C lowering effects among individuals who were not receiving statin therapy mainly because of statin intolerance. Methods: The Phase 3 ORION-10 and ORION-11 trials randomized patients with established ASCVD (or risk-equivalents) with LDL-C >70 mg/dl despite maximally tolerated statins to inclisiran or placebo (1:1). Inclisiran sodium 300 mg was administered s.c. at baseline, three months later, then every six months. The primary efficacy endpoints were % change in LDL-C from baseline to Day 510 and time adjusted % change in LDL-C from baseline after Day 90 and up to Day 540. Absolute LDL-C reductions were secondary endpoints. This analysis included individuals who were not on statin therapy at baseline. Results: The trials included 252 (7.9% of the pooled trial populations; mean age 68; male 62%; lipid-lowering therapy 28%). AE rates and LDL-C reductions are shown in the Table. Overall, 12 (4.7%) patients had myalgia (4.8% in the inclisiran groups, 4.7% in the placebo groups). There were 8 discontinuations in the inclisiran groups (6.5%) and 3 in the placebo groups (2.3%). The placebo-adjusted mean reduction in LDL-C at Day 510 was 45.8%, an absolute reduction of 68.0 mg/dL (p<0.0001). Conclusion: Among statin intolerant individuals in ORION-10 and 11, inclisiran potently and durably lowered LDL-C with an adverse event profile comparable to placebo. Inclisiran may represent a new and potent therapeutic option for patients with elevated LDL-C unable to tolerate statins. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): The Medicines Company